Photochemistry of framework-supported M(diimine)(CO)₃X complexes in 3D Lithium-Carboxylate metal−organic frameworks: monitoring the effect of framework cations - Reade, Thomas J.; Murphy, Thomas S.; Calladine, James A.; Horvath, Raphael; Clark, Ian P.; Greetham, Gregory M.; Towrie, Michael; Lewis, William; George, Michael W.; Champness, Neil R. (Royal Society of Chemistry, 2017)
The structures and photochemical behaviour of two new metal-organic frameworks are reported. Reaction of Re(2,2ʹ-bipyʹ-5,5ʹ-dicarboxylic acid)(CO)₃Cl or Mn(2,2ʹ-bipyʹ-5,5ʹ- dicarboxylic acid)(CO)₃Br with either LiCl or LiBr, respectively, produces single crystals of {Li₂(DMF)₂[(2,2ʹ-bipyʹ-5,5ʹ-dicarboxylate)Re(CO)₃Cl]}n (ReLi) or {Li₂(DMF)₂[(2,2ʹ-bipyʹ- 5,5ʹ-dicarboxylate)Mn(CO)₃Br]}n (MnLi). The structures formed by the two MOFs comprise one-dimensional chains of carboxylate-bridged Li(I) cations that are cross-linked by units of Re(2,2ʹ-bipyʹ-5,5ʹ-dicarboxylate)(CO)₃Cl (ReLi) or Mn(2,2ʹ-bipyʹ-5,5ʹ- dicarboxylate)(CO)₃Br (MnLi). The photophysical and photochemical behaviour of both ReLi and MnLi are probed. The rhenium-containing MOF, ReLi, exhibits luminescence and the excited state behaviour, as established by time-resolved infra-red measurements, are closer in behaviour to that of unsubstituted [Re(bipy)(CO)₃Cl] rather than a related MOF where the Li(I) cations are replaced by Mn(II) cations. These observations are further supported by DFT calculations. Upon excitation MnLi forms a dicarbonyl species which rapidly recombines with the dissociated CO, in a fashion consistent with the majority of the photoejected CO not escaping the MOF channels.